Trash @ School - Coelho, A.; Moleiro, M. C. (Open Schools Journal for Open Science, 2020)
After the inauguration of a local park located next to Venda do Pinheiro school, students quickly began to encounter problems of misuse. Specifically, they complained about garbage scattered in a park that was still new: cigarette butts in the skate and sports areas, dog waste, and other situations. The aim of this project was to challenge students to find solutions to make park users aware of how to improve their behavior. After identifying this common problem, each group had to design a multimedia product to raise public awareness, either by creating a video campaign or designing a piece of urban furniture using 3D modeling and printing.